Model Komunikasi Pendidikan dalam Menumbuhkan Kesadaran dalam Menghindari Praktik Bullying di SMA Negeri 2 Bireuen - Hasna Yarita; Dwi Fitri; Jafaruddin; Awaluddin Arifin; Bobby Rahman (CV. Ulil Albab Corp, 2026)
The theoretical foundation of this study is based on the concept of educational communication, which views the learning process as a form of interaction between the communicator (teacher) and the communicant (students), where moral messages and social values are conveyed to shape the character of the learners. This research refers to harold d. Lasswell’s communication model, which consists of five simple stages: who, says what, in which channel, and to whom in achieving effective educational communication. This study is also grounded in law number 20 of 2003 on the national education system, which emphasizes that education aims to develop students’ potential to become individuals who are faithful, virtuous, and responsible. This research uses a qualitative approach with a case study method, and employs harold d. Lasswell’s communication model as the main analytical framework. The findings show that educational communication at SMA Negeri 2 Bireuen is carried out through teachers’ persuasive approaches, counseling services, the integration of moral values in learning activities, and the use of media such as banners and posters. The educational communication model implemented at SMA Negeri 2 Bireuen is integrative and humanistic in nature